Sedentarisation of cattle farmers in the derived savanna region of south west Nigeria: Results of a survey - Jabbar, M.A.; Reynolds, L.; Francis, P.A. (Springer, 1995)
The aim of this study was to assess the process and extent of sedentarisation among Fulani cattle owners in the derived savannah zone of south-west Nigeria. The results, based on a survey of 66 randomly-selected cattle owners, indicate an on-going process of settlment. Previously cattle owners visited the zone for dry season grazing but an increasing number were found to be settling and becoming mixed livestock/crop farmers. Generally herd sizes were larger among recent settlers but with longer duration of settlement and with cattle rearers' involvement in crop production, the herds became less mobile between seasons and herd size decreased and the proportion of farms with mixed Zebu/trypanotolerant cattle herds increased. There was also evidence that some indigenous Yoruba crop farmers were becoming mixed farmers by purchasing cattle, hiring Fulani herdsmen for management, then taking up the management themselves.